Harbingers of child abuse: A complex healthcare issue for dentistry - Amandeep Chopra; Nidhi Gupta; Nanak Chand Rao; Shelja Vashisth (Wolters Kluwer Medknow Publications, 2013)
Child abuse or maltreatment constitutes all forms of physical and/or emotional ill-treatment, sexual abuse, neglect or negligent treatment or commercial or other exploitation, resulting in actual or potential harm to the child's health, survival, development or dignity in the context of a relationship of responsibility, trust or power. It permeates all ethnic, cultural and socio-economic segments of our society. Child abuse is a vicious cycle in which victims are at higher risk of becoming abusive parent repeating their childhood experiences. Studies have shown that approximately 60-75% of abused children have injuries to the head, face and mouth. Dentists are in the unique position to be able to diagnose these cases. The complete information about child abuse has been collected from various journals, books, online databases and various reports from international conferences for the time period of 1988-2012. This article presents an overview of child abuse, its types, identification and reporting of cases of abuse.